Performance evaluation of cement concrete containing sandstone slurry. (30th September 2018) - Arif, Mohmmad; Gupta, Vinayak; Choudhary, Harsh; Kumar, Sanjeev; Basu, Prarthita
Highlights: Suitability of sandstone slurry as total replacement of aggregates has been studied. M20 grade of concrete was used for the study to determine durability. An equivalent result of sulphate resistance was observed with respect to OPC concrete. Abstract: Durability is one of the primary concern in new buildings and also for the old existing infrastructures. This paper deals with the durability properties of concrete containing sandstone slurry as a filler material. A significant quantity of sandstone slurry gets deposited, and their disposal problem becomes acuter. In order to utilize these wastes and to practice a sustainable construction, the ultimate solution is to use these types of sandstone slurry in concrete. Since durability plays an enormous role in maintaining the infrastructure for years, various tests such as compressive strength, flexural strength, water absorption, sulfate attack, acid attack, carbonation, DIN-Permeability, sorptivity are done to get the durability of the sandstone slurry mix in concrete. This paper presents the result of experimental research to examine the suitability of sandstone slurry as a partial replacement of total aggregates in cement concrete. It was observed that up to a certain level of substitution, compressive and flexural strength show a comparable result to that of control concrete. Also, it shows a good result with a controlled replacement towards acid-attack as well as sulfate attack and are equivalent to that of Portland cement concrete. Similar effect were also observed towards carbonation and permeability. From the results, it can be said that there is a promising future for the use of sandstone slurry as a partial replacement of total aggregate, which can lead to more significant environmental and sustainable benefits.